2005
DOI: 10.2466/pms.101.1.90-94
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Directionality and Orientation in Drawings by Young Children and Adults

Abstract: The present study examined the relationship between directionality of drawing movements and the orientation of drawn products in right-handed adults and young children for 27 Japanese kindergartners and 29 Japanese university students who were asked to draw with each hand fishes in side view and circles from several starting points. Significant values of chi2 for distributions of frequencies of orientation of the fish drawings and the direction of circular drawing movement indicated that adult right-handers dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…As differences in drawing movements by the participants from the two countries were found only when the dominant hand was used, the findings of the present study supported the expectations and were consistent with the previous related studies (e.g., Vinter & Meulenbroek, 1993;Taguchi & Noma, 2005). Adults have been heavily exposed and accustomed to the writing habits of their languages, so the bias on the starting positions and directionality of drawing was likely well established for the dominant hand (Vaid, 1995).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As differences in drawing movements by the participants from the two countries were found only when the dominant hand was used, the findings of the present study supported the expectations and were consistent with the previous related studies (e.g., Vinter & Meulenbroek, 1993;Taguchi & Noma, 2005). Adults have been heavily exposed and accustomed to the writing habits of their languages, so the bias on the starting positions and directionality of drawing was likely well established for the dominant hand (Vaid, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Some researchers have suggested that reading and writing habits may influence fine motor skills such as writing and drawing movements (e.g., Vaid, Maharaj, Sakhuja, & Gupta, 2002;Fagard & Dahmen, 2003;Taguchi & Noma, 2005). Vaid, et al (2002) asked native readers of Hindi (a language read and written from left to right) and Urdu (a language read and written from right to left), ages 15 to 20 years, to draw five objects such as an arrow or a pencil, with the dominant hand, and observed the direction of the stroke employed in drawing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional variable here may be that when using the right hand lateral movements are easier to make in a left to right direction. Taguchi and Noma (2005) studied 20 right-handed Japanese adults on a fish drawing and circle drawing task performed with each hand. They found an overall left facing bias which was stronger when the right hand was used; further, a relationship was found between left-facing of the fish and the use of a clockwise movement in circle drawing, but only when the right hand was used.…”
Section: Dominant Vs Non-dominant Hand Usedmentioning
confidence: 99%
“…The circle was drawn counter-clockwise by the majority of children. This behavior of giving priority to counter-clockwise (CC) directionality over clockwise (C) has been frequently found in Western graphonomic studies for circle drawing ( van Sommers, 1989 ;Taguchi & Noma, 2005 ;Tabatabaey-Mashadi, et al ., 2013 ). The uniformity of circle drawing may also be related to its particular shape that is already established in principle within this age group.…”
Section: Directionalities In Drawing Performancementioning
confidence: 57%